Arsenite removal from groundwater by aerated electrocoagulation reactor with Al ball electrodes: Human health risk assessment - Goren, A. Y.; Kobya, M.; Oncel, M. S. (Pergamon-Elsevier Science Ltd, 2020)
The application of conventional electrocoagulation (EC) process for removal of As(III) from groundwater suffers from the need of external oxidation agent for oxidation of As(III) to As(V). To tackle this limitation, an aerated EC reactor for the removal of As(III) from groundwater was evaluated in this study. The effect of initial pH(i), air flow rate, applied current, and electrode height in the EC reactor was examined. The experimental results showed that removal of arsenic mostly dependent on the applied current, electrode height in EC reactor, and air flow rate. The As(III) removal efficiency (99.2%) was maximum at pH(i) of 7.5, air flow rate of 6 L min(-1), applied current of 0.30 A, and electrode height in EC reactor of 5 cm, with an total operating cost of 0.583 $ m(-3). Furthermore, the carcinogenic risk (CR) and non-carcinogenic risk of arsenic (As) was in the range of tolerable limits at all operating conditions except applied current of 0.075 A at the end of the aerated EC process to remove As from groundwater. The present EC reactor process is able to remove As(III) from groundwater to below 10 mu g L-1, which is maximum contaminant level of arsenic in drinking water according to the World Health Organization (WHO). (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: Arsenite; Electrocoagulation; Aerated reactor; Al ball electrodes; Risk assessment